Poverty, Racism, and the Public Health Crisis in America - Beech, Bettina M.; Ford, Chandra; Thorpe, Roland J.; Bruce, Marino A.; Norris, Keith C. (Frontiers in Public Health, 2021)
The purpose of this article is to discuss poverty as a multidimensional factor influencing health. We will also explicate how racism contributes to and perpetuates the economic and financial inequality that diminishes prospects for population health improvement among marginalized racial and ethnic groups. Poverty is one of the most significant challenges for our society in this millennium. Over 40% of the world lives in poverty. The U.S. has one of the highest rates of poverty in the developed world, despite its collective wealth, and the burden falls disproportionately on communities of color. A common narrative for the relatively high prevalence of poverty among marginalized minority communities is predicated on racist notions of racial inferiority and frequent denial of the structural forms of racism and classism that have contributed to public health crises in the United States and across the globe. Importantly, poverty is much more than just a low-income household. It reflects economic well-being, ability to negotiate society relative to an individual’s education, socioeconomic or health status, as well as social exclusion based on institutional policies, practices, and behaviors. Until structural racism and economic injustice can be resolved, the use of evidence-based prevention and early intervention initiatives to mitigate untoward effects of socioeconomic deprivation in communities of color such as the use of social media/culturally concordant health education, social support such as social networks, primary intervention strategies and more will be critical to address the persistent racial/ethnic disparities in chronic diseases.